Hubungan Masyarakat di SMA Antartika Sidoarjo : Strategi untuk Meningkatkan Kolaborasi Internal dan Eksternal - Imroatuz Zulfa; Vira Aurelia Fanesa; Annisa Tri Agustina; Khairunnisa Nur Afifah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This research aims to explore the role and strategy of community relations at SMA Antartica Sidoarjo in improving internal and external collaboration. Effective public relations can strengthen communication between schools, students, parents and communities, and create an environment that supports the teaching and learning process. The research method used is a qualitative approach with data collection techniques through interviews, observation and document analysis. The research results show that Antarctica High School has implemented various public relations strategies, such as organizing collaborative events, utilizing social media, and partnership programs with external institutions. It is hoped that these findings can become the basis for developing further strategies to strengthen collaboration and improve the quality of education at Sidoarjo Antarctic High School.